2019
DOI: 10.1063/1.5125252
|View full text |Cite
|
Sign up to set email alerts
|

Accurate phase retrieval of complex 3D point spread functions with deep residual neural networks

Abstract: Phase retrieval, i.e. the reconstruction of phase information from intensity information, is a central problem in many optical systems. Here, we demonstrate that a deep residual neural net is able to quickly and accurately perform this task for arbitrary point spread functions (PSFs) formed by Zernike-type phase modulations. Five slices of the 3D PSF at different focal positions within a two micron range around the focus are sufficient to retrieve the first six orders of Zernike coefficients.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
(26 reference statements)
0
31
0
Order By: Relevance
“…It was our goal to combine a compact architecture to enable rapid, real-time PR with large Zernike coefficient amplitude ranges. [102] Additionally, we wanted to ensure that the approach is purely based on the NN, i.e. that there is no requirement for refinement of the predictions of the NN.…”
Section: Psf Analysis For Extraction Of Molecular and Imaging Parametersmentioning
confidence: 99%
“…It was our goal to combine a compact architecture to enable rapid, real-time PR with large Zernike coefficient amplitude ranges. [102] Additionally, we wanted to ensure that the approach is purely based on the NN, i.e. that there is no requirement for refinement of the predictions of the NN.…”
Section: Psf Analysis For Extraction Of Molecular and Imaging Parametersmentioning
confidence: 99%
“…The emergence of deep learning has revolutionized the field of image processing. In particular, methods have been proposed for the deblurring of video sequences (Wieschollek et al 2017), for the rapid estimation of PSFs from images (Möckl et al 2019), and for the modeling of simple PSFs (Herbel et al 2018) for large-scale surveys. It is evident that methods that make use of many frames to produce a single deconvolved frame make much better use of the collected photons and should always be preferred over lucky imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, deep learning-based approaches using convolutional neural networks (CNNs) have proven to be powerful and computationally efficient for image-based classification and regression tasks for microscopy images [18,19]. Recently, several studies demonstrated that deep learning-based phase retrieval can produce accurate results at fast processing speeds [20][21][22][23][24][25], however they fall short regarding their practical applicability. Some of these approaches [22][23][24] used purely simulated synthetic data, where generalizability to real microscopy images is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies demonstrated that deep learning-based phase retrieval can produce accurate results at fast processing speeds [20][21][22][23][24][25], however they fall short regarding their practical applicability. Some of these approaches [22][23][24] used purely simulated synthetic data, where generalizability to real microscopy images is unclear. Others focused on specific microscopy acquisition modes (such as using biplanar PSFs [20]) or microscopy setups that allow to collect large sets of experimental ground truth data for training and prediction [21,25], thus limiting this approach in practice.…”
Section: Introductionmentioning
confidence: 99%